Efeitos da associação dos tratamentos de crioterapia e ultrassom terapêutico na reparação da lesão muscular de ratos wistar - Koike, Tatiana Emy [UNESP] (2016)
Muscle injuries are often cause due to the practice of sports and recreational activities. Because of its high incidence, it is important to research the treatments that promote quality in the muscle and shorter repair process. To evaluate the effect of the combination of the therapeutic resources of Cryotherapy and Therapeutic Ultrasound in the treatment of muscle damage by impact. 55 Wistar rats was separate into groups, Acute Injury (AI), Injury (I), Cryotherapy (CR), Therapeutic Ultrasound (TU), Cryotherapy and Therapeutic Ultrasound (CRTU). All animals were anesthetize and muscle damage due to impact by the release of a load of 200 g at 30 cm. Then received treatments as allocated group and CR protocol using ice bag for 20 minutes and TU for five minutes with an intensity of 0.5W / cm2 and the frequency of 1MHz. Euthanasia was performed by intraperitoneal administration of overdose of Xylazine and Ketamine. The collection of the gastrocnemius muscle for the Body and Muscle mass analysis, histological analysis and fractal dimension of inflammation and collagen gene quantification of mRNA (TNF-α and TGF-β1). Data analysis was performed using SPSS for Windows 22. The Shapiro-Wilk test to verify the normality of the data was performed. When data showed normal, we used t test for paired samples test and one-way ANOVA followed by Tukey’s post-test. When it violated the normality of the data, followed by the Kruskal- Wallis test with Dunn’s post-test. For all analyzes was adopted the significance level of 5%. Among all groups, the CRTU lose less body and muscle mass, improved morphometry, besides presenting collagen reduction by DF compared to AI and CR (p <0.05). With regard to the inflammatory process CRTU group showed a significant reduction of DF in relation to the AI groups (p = 0.001), I (p = 0.001) and CR (p = 0.007), and TU reduced the DF significantly relative to AI groups (p = 0.001), I (p = 0.001) and CR (p = 0.036). The reduction of TNF-α was significant in TU group compared with AI groups (p = 0.008); I (p = 0.032) and CR (p = 0.046) and TGF- β1 in the CR group compared to AI (p = 0.001) and I (p = 0.006), in the TU group compared to AI (p = 0.049) and CRTU compared to AI (p = 0.023). The combination treatment was superior to the results presented by the isolated treatments in the muscle repair process. Observed by reducing the loss of body and muscle mass, improved histological appearance and reduction of collagen.